KEMAMPUAN ISOLAT BAKTERI PEMBINTIL AKAR LEGUM DALAM PEMBENTUKAN BINTIL AKAR DAN PENAMBATAN NITROGEN PADA TANAMAN KEDELAI (Glycine max) DI TANAH GAMBUT - , WINDA ANDRIANI M, Ir. Sri Wedhastri., MS. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The objective of this study was to select legume nodulating bacteria isolates based on their ability to form nodules and fix nitrogen on soybean (Glycine max) grown in peat soil using seed treatment method. The ability to fix nitrogen was analyzed by ARA (Acetylene Reduction Assay). This study used 44 soybean nodulating bacteria isolates, collection of the Department of Microbiology, Gadjah Mada University. These isolates were assayed and compared to two positive controls i.e Bradyrhizobium japonicum USDA 122 and Bradhyrhizobium japonicum THA 7. Uninoculated soybean grown either on fertilized and unfertilized peat soil were used as negative controls. Legume nodulating bacteria which have both ability to nodulate as well as to fix nitrogen were examined to nodulate and fix nitrogen on soybean grown on peat soil ameliorated with dolomite. Uninoculated soybean grown either on ameliorated-fertilized and ameliorated-unfertilized peat soil were used as negative controls. The result showed that 11 bacterial isolates had ability to nodulate soybean grown on peat soil. The isolates were H 2.4, HT 1.1, HT 3.2, RT 1.2, RT 1.3, RT 2.1, RT 2.3, RT 3.2, RT 3.3, RT 3.4, P 2.1, however only seven isolates which produced nodules had ability to fix nitrogen i.e H 2.4, HT 3.2, RT 1.2, RT 2.3, RT 3.3, RT 3.4 and Bradyrhizobium japonicum USDA 122. Bradhyrhizobium japonicum THA 7 was able to produce nodules but it was not able to fix nitrogen. When these isolates examined to nodulate and fix nitrogen on soybean grown on ameliorated peat soil, the result showed that seven isolates had ability to nodulate soybean, however only two isolates which produced nodules had ability to fix nitrogen i.e RT 3.3 and RT 3.4. Bradyrhizobium japonicum USDA 122 and Bradhyrhizobium japonicum THA 7 was able to produce nodules but it was not able to fix nitrogen. Based on the result, it could be concluded that there were legume nodulating bacteria isolates which could survive, form root nodules and fix nitrogen on soybean grown on peat soil either with and without ameliorant.